Evaluation the Application Status of GAAP in Financial Reporting Practice: In Case of Banking Sector in Bangladesh - Banu, Mst. Hasna; Sayaduzzaman, Md.; Sil, Subhash Chandra (Asian Business Review, 2021)
The prime concentration of this study is to scan the respondents’ opinions regarding the application status of the different units of GAAP in preparing the different financial reports by the sample banks. To meet this objective an attempt has been made to collect opinions from one hundred fifty respondents comprising of fifty chartered accountants, fifty cost and management accountants as well as fifty academicians. Frequency analysis has been used to evaluate their perceptions. The result of frequency analysis reveals that the sample banks greatly apply the accounting entity assumption, going concern assumption, assumption of a stable momentary unit as well as time period assumption in preparing the financial statements. Furthermore, this study has likewise employed ANOVA as well as Chi-square techniques to investigate whether there is any significant deviation amidst the respondents’ opinion concerning the execution of different segments of GAAP for financial reporting practice of the sample banks and the outcomes indicate that there is the significant difference among the respondents’ opinion regarding the application status of the different units of GAAP in financial reporting practice by the sample banks in some cases and in other cases the difference of opinion has also been observed.
Keywords: Financial Statements; GAAP; State-Owned Commercial Banks; Bangladesh